Computer vision : algorithms and applications (Texts in computer science, 2011)
Humans perceive the three-dimensional structure of the world with apparent ease. This title explores the variety of techniques commonly used to analyze and interpret images. It also describes challenging real-world applications where vision is being successfully used, both for specialized applications such as medical imaging, and for fun